Effects of Crumb Rubber on the Shear Strength of Sand: An Experimental Study - Sung, Brandon Hon Kong; Wong, Soon Yee; Cyril, Perpetua Aaniya; Lee, Min Lee; Mohamed, Abdullahi Ali (Advances in Technology, 2022)
The application of waste rubber tires for ground improvement helps to improve the environment by recycling and reusing it as admixtures. This research aims to investigate the shear strength parameters of rubber-sand mixtures. By using crumb rubber with a constant size (425μm), the sand is replaced by different percentages (0, 2.5, 5.0, 7.5, and 10%) of crumb rubber by weight. A direct shear box test is used to determine the shear strength parameters of rubber-sand mixtures with two different controlled densities. The samples were loaded with normal stresses of 20, 40 and 80kPa and were sheared at a rate of 1mm/min. Although, this experiment discovered that crumb rubbers improve the shear strength parameters in loose sand, however, a reduction in shear strength parameters was found in dense sand. Moreover, it was observed that the inclusion of crumb rubbers into sand greatly improve the strain energy of both loose and dense sand. Likewise, rubber has a low unit weight which makes it suitable for lightweight backfill materials. The surface properties of rubber should be further studied to understand the contribution of shear strength in the rubber-sand mixture.